Nano-zinc and plant growth-promoting bacteria is a sustainable alternative for improving productivity and agronomic biofortification of common bean - Jalal, Arshad [UNESP]; Mortinho, Emariane Satin [UNESP]; da Silva Oliveira, Carlos Eduardo [UNESP]; Fernandes, Guilherme Carlos [UNESP]; Junior, Enes Furlani [UNESP]; de Lima, Bruno Horschut [UNESP]; Moreira, Adônis; Nogueira, Thiago Assis Rodrigues [UNESP]; Galindo, Fernando Shintate [UNESP]; Filho, Marcelo Carvalho Minhoto Teixeira [UNESP] (Springer Nature, 2023)
Background and aims: Nano-zinc (Zn) fertilizer is an easily adaptable and environmentally safe alternative option that can effectively improve growth, yield and biofortification of common bean. Plant growth-promoting bacteria (PGPBs) could promote plant growth and nutrients availability in sustainable manner. Therefore, this study aimed to investigate the influence of foliar nano-Zn application in association with seed co-inoculations of PGPBs on growth, yield, biofortification and Zn use efficiencies in common bean cultivation. Two field experiments were performed with seven co-inoculations of PGPBs and three foliar nano-Zn doses applied 50% at R5 and 50% at R8 stages of common bean to determine plant height, shoot dry matter, grain yield, Zn concentration and uptake in shoot and grains, Zn partitioning index, daily Zn intake and Zn use efficiencies for agronomic biofortification. Results: The combined foliar nano-Zn application and co-inoculation of R. tropici + B. subtilis enhance grain yield, leaf chlorophyll index, total protein content, grain Zn concentration and uptake, daily Zn intake, Zn use efficiency, applied Zn recovery and Zn utilization efficiency in common beans in 2019 and 2020 cropping seasons. Foliar nano-Zn application at a dose of 1.5 kg ha−1 increased plant height, shoot dry matter, shoot Zn uptake, Zn partitioning and agro-physiological efficiency under co-inoculation with R. tropici + B. subtilis in both cropping years. Conclusions: The treatments with foliar nano-Zn application at a dose of 1.5 ha−1 and co-inoculation with R. tropici + B. subtilis improved performance, chlorophyll index, protein content, grain yield, and Zn efficiencies that can lead to better biofortification of common bean in tropical savannah. Therefore, it is recommended that applying nano-Zn via foliar along with co-inoculation of PGPBs could be the better option for productivity and biofortification of common bean. Graphical Abstract: [Figure not available: see fulltext.].
Keywords: Agronomic biofortification; Foliar nano-zinc; PGPBs; Zinc partitioning; Zinc uptake; Zinc use efficiencies